Relationship between Health Literacy and Determinants of Pap Smear Test Based on the Protection Motivation Model - Seyedeh gissia Fakhrelkoneini; Afshin Bahmani; Sairan Nili; Tahereh Pashaei (Mazandaran University of Medical Sciences, 2024)
Introduction and purpose: Cervical cancer is the second most common cancer among females, and one of the influential factors in the course of cervical cancer is the health literacy of patients. This study aimed to determine the relationship between health literacy and determinants of performing Pap smear tests based on the Protection Motivation Model. Methods: A sectional study was conducted on eligible females visiting the health center in the city of Muchesh, Iran in the year 2022. In total, 216 individuals were selected through a census. Data collection was performed using the Population Information Questionnaire, the Health Literacy Assessment Tool for the urban population of Iran (18-65 years old), and the Structured Questionnaire of Motivational Protection Theory. The collected data were entered into SPSS software (version 22), and analysis was carried out using descriptive statistics, the Kolmogorov-Smirnov test, analysis of variance, and Pearson correlation. The significance level was considered at P < 0.05. Results: The study results showed that the mean scores of health literacy, reading comprehension, access, perception, evaluation, and decision-making were 84.24 ± 9.30, 18.28 ± 6.30, 78.29 ± 4.30, 65.27 ± 9.31, 21.24 ± 6.31, and 29.25 ± 7.30, respectively. Health literacy had a significant relationship with the perceived severity score, perceived susceptibility score, perceived response efficacy score, perceived self-efficacy score, perceived rewards score, and the overall score (P<0.05). However, health literacy had no relationship with the perceived sensitivity score, perceived response cost score, and protection motivation score. Conclusion: Women's health literacy has a direct and significant impact on some of the determinants of Pap smear test performance. In other words, women with higher levels of health literacy are more inclined to undergo Pap smear tests.